COMPOSIÇÃO NUTRICIONAL E CUSTO DE PREPARAÇÕES DE RESTAURANTES POR PESO - Ana Clara Martins e Silva Carvalho; Hélia Cristina do Couto Cabral; Mariana Patrício de Morais (Universidade do Estado do Rio de Janeiro, 2013)
The lack of nutrition facts regarding to foods sold for restaurants can jeopardize people's choices. This paper aims to describe the nutrition facts availability in restaurants in Sao Paulo city, Brazil, according to the kind of establishment and socioeconomic level of the administrative district. Descriptive study, with data collection was undertaken in all full service and fast food restaurants in 13 districts of the city of Sao Paulo, which were chosen according to the Municipal Human Development Index and food environment variables. In each district, 4 census tracts were chosen, yielding 52 census tracts. In total, 472 restaurants were found and assessed. Most of them (45.5%) were classified as bars, delis, and convenience stores. One tertile (30.3%) were local and large chain fast food restaurants and 24.2% were full service restaurants. Nutrition facts were found in 5 restaurants (1.1%), all part of large chain fast food companies and situated in districts with higher socioeconomic level. Nutrition facts in restaurants were found to be very scarce, bringing about the need for policies to regulate the availability of nutrition facts for the population.